Cholesterol's Function and Origin in the Alzheimer's Disease Brain - Hansen, Scott B (Journal of Alzheimer's disease, 2023)
Alzheimer's disease (AD) is a neurodegenerative disorder associated with neuroinflammation and altered lipids in the brain. Cholesterol is a key component of inflammatory lipids. However, the role of cholesterol in AD, specifically in sporadic or late-onset AD, has remained poorly understood due to the belief that most brain cholesterol is separate from circulating blood cholesterol. A new theory suggests that the permeation of circulating cholesterol into the brain is a causal event critical for the onset of AD. As research in this area continues, new hypotheses and insights into AD are expected to emerge.